Plantas aquáticas e nível de infestação das espécies presentes no reservatório de Barra Bonita, no rio Tietê - Carvalho, F.t. [UNESP]; Galo, M.l.b.t. [UNESP]; Velini, E.d. [UNESP]; Martins, D. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2003)
Aquatic vegetation inventory allows to evaluate community evolution and to determine the potential of damages associated to these populations. The objective of this work was to identify the aquatic plants and the infestation levels of each species in the Barra Bonita reservoir. All the aquatic vegetation focuses in the dam (335 points) were evaluated and marked with a GPS apparel. The plants were identified and a visual estimate of the geographical value of the point (size of the area) and a proportional distribution of the plants in the focus were carried out. It was observed that the area occupied by the dam, estimated by the Landsat image was of 277.180.000 m² and the area occupied by the superficial aquatic vegetation was of 18.710.000 m². Seventeen macrophyte species were found vegetating in the Barra Bonita dam. Due to great diversity of species found, those presenting infestation levels above 10% were considered to be the main ones ones, i.e, Brachiaria mutica, Brachiaria subquadripara and Eichhornia crassipes. Other species considered outstanding in the inventory, with indices from 5% to 10%, were: Pistia stratiotes, Enidra sessilis, Polygonum lapathifolium, Echinochloa polystachya and Salvinia auriculata.

O monitoramento da vegetação aquática permite avaliar a evolução das comunidades e determinar o potencial de danos associados a essas populações. O objetivo do trabalho foi identificar as plantas aquáticas e os níveis de infestação de cada espécie, presentes no reservatório de Barra Bonita. Foram avaliados todos os focos de vegetação aquática presentes na represa (335 pontos), sendo os pontos demarcados com um aparelho de GPS. As plantas foram identificadas e foi feita uma estimativa visual de valor geográfico do ponto (tamanho da área) e distribuição proporcional das plantas no foco. Observou-se que a área ocupada pela represa, estimada a partir da imagem Landsat, foi de 27.718 ha e que a área ocupada por macrófitas superficiais foi de 1.871 ha. Foram encontradas 17 espécies macrófitas vegetando na represa de Barra Bonita. Em razão da grande diversidade de espécies encontradas, considerou-se que as principais foram as que ocorreram com níveis de infestação acima de 10%. Portanto, as espécies aquáticas mais importantes foram: Brachiaria mutica, Brachiaria subquadripara e Eichhornia crassipes. Outras espécies que podem ser destacadas no levantamento, com índices entre 5 e 10%, foram: Pistia stratiotes, Enidra sessilis, Polygonum lapathifolium, Echinochloa polystachya e Salvinia auriculata.
Aquatic plants and level of infestation of the species at the Barra Bonita reservoir in the Tietê river
Keywords: aquatic vegetation; inventory; dam; macrófitas; monitoramento; represa